2019
DOI: 10.1038/s41577-019-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Defining ‘T cell exhaustion’

Abstract: The contributors Christian U. Blank is a medical oncologist and principal investigator at the Netherlands Cancer Institute. He is Professor of Haematology/oncology at the university of Regensburg, Germany, and received an MBA degree from the university of Warwick, UK. His research interests include neoadjuvant immunotherapies, targeted and biological response modifiers, and prognostic markers for cancer immunotherapies. W. Nicholas Haining is a physician-scientist and vice-President for Discovery oncology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
907
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,096 publications
(944 citation statements)
references
References 65 publications
(216 reference statements)
30
907
4
3
Order By: Relevance
“…Studies using models of chronic viral infections show that T-cell exhaustion helps to balance the immune response to infection and immunopathology to the host. 237 Emerging studies suggest that mTOR In addition to exhaustion driven by repeated antigen stimulation, T cells may also become metabolically exhausted, in which nutrient insufficiency or other metabolic stressors program cells to adopt a dysfunctional state irrespective of their antigen specificity.…”
Section: Mtor Signaling In T-cell Exhaustionmentioning
confidence: 99%
“…Studies using models of chronic viral infections show that T-cell exhaustion helps to balance the immune response to infection and immunopathology to the host. 237 Emerging studies suggest that mTOR In addition to exhaustion driven by repeated antigen stimulation, T cells may also become metabolically exhausted, in which nutrient insufficiency or other metabolic stressors program cells to adopt a dysfunctional state irrespective of their antigen specificity.…”
Section: Mtor Signaling In T-cell Exhaustionmentioning
confidence: 99%
“…The relevance of chronic versus acute infection is also an important area to consider, as chronic infections tend to induce T‐cell exhaustion (Blank et al, ; Wherry & Kurachi, ). We suggest that the acute nature of L. monocytogenes infection is an additional feature responsible for inducing a favourable environment for the induction of CMI because it does not lead to T‐cell exhaustion.…”
Section: Future Directionsmentioning
confidence: 99%
“…While the presence of tumor-infiltrating T lymphocytes (TILs) in cancer lesions has been broadly associated with improved prognosis and response to immune checkpoint blockade 5,6 , scRNA-seq has uncovered a great diversity within TILs, revealing that distinct TIL states contribute differently to tumor control and response to immunotherapies [7][8][9] . Crucially, antigen persistence in cancer and chronic infections profoundly alters CD8 T cell differentiation and function, leading antigen-specific cells into a collection of states referred to as "exhaustion" 10 . Recent data has shown that exhausted CD8 T cells are phenotypically and functionally heterogeneous [11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%